Safety of sofosbuvir‐based regimens after liver transplantation: longitudinal assessment of renal function in the prospective ANRS CO23 CUPILT study. Issue 12 (17th April 2018) - Anty, R.; Favre, G.; Coilly, A.; Rossignol, E.; Houssel‐Debry, P.; Duvoux, C.; De Ledinghen, V.; Di Martino, V.; Leroy, V.; Radenne, S.; Kamar, N.; Canva, V.; et al.
Summary: Background: In liver transplant recipients with hepatitis C virus recurrence, there is concern about renal safety of sofosbuvir‐based regimens. Changes in serum creatinine or in the estimated glomerular filtration rate (eGFR) under treatment are used to look for possible renal toxicity. However, serum creatinine and eGFR are highly variable. Aim: To analyse renal function trajectory with numerous assays of serum creatinine over a long period of time. Methods: In a multicentre cohort of 139 patients, the eGFR was obtained from serum creatinine using the Chronic Kidney Disease–Epidemiology Collaboration (CKD‐EPI) equation. Slopes of eGFR were defined as a change in eGFR during a period divided by time. Pre‐treatment, on‐treatment and post‐treatment periods were 9 months, 3‐9 months and 4.5 months. Interactions between eGFR slopes and the pre‐treatment eGFR, use of ribavirin or mycophenolate mofetil, and stage of fibrosis were addressed. On‐treatment eGFR slopes were separated in tertiles. Pre‐ and post‐treatment eGFR slopes were compared globally and according to tertiles. Results: The post‐treatment eGFR slope was significantly better than pre‐treatment eGFR slope (+0.18 (IQR −0.76 to +1.32) vs −0.11 (IQR −1.01 to +0.73) mL/min/1.73 m 2 /month, P = 0.03) independently of the pre‐treatment eGFR ( P = 0.99), ribavirin administration ( P = 0.26), mycophenolate mofetil administration ( P = 0.51) and stage of fibrosis (F3 and F4 vs lower stages, P = 0.18; F4 vs lower stages, P = 0.08; F4 Child‐Pugh B and C vs lower stages, P = 0.38). Tertiles of on‐treatment eGFR slopes were −1.71 (IQR −2.54 to −1.48), −0.78 (IQR −1.03 to −0.36) and +0.75 (IQR +0.28 to +1.47) mL/min/1.73 m 2 /month. Pre‐ and post‐treatment eGFR slopes were not significantly different according to tertiles (respectively, P = 0.34, 0.08, 0.73). Conclusion: The eGFR varies during treatment and gives a confusing picture of the renal safety of sofosbuvir‐based regimens. In contrast, longitudinal assessment of the eGFR shows a rising trajectory over longer time, meaning that these therapies are safe for the kidneys in our cohort of liver transplant recipients.